As estratégias percebida por empresas gaúchas sob o enfoque teórico do posicionamento, da visão baseada em recursos, da missão e da tipologia - Capalonga, Giovani (Universidade do Vale do Rio do Sinos, 2008)
This dissertation is addressing the strategy perceived by business in the south Brazilian. Recent studies examining the connections between the Strategic Positioning, the Vision Based on Resources - RBV, the Strategic Mission and Strategic Typology are based on theoretical constructions or in case studies. This dissertation seeks to contribute to the consolidation of the subject. For this theoretical framework aimed at the concepts of strategy, the perceived strategy of strategic content, the concept of approaches to Strategic Positioning, the Vision Based on Resources - RBV, the Mission and the Strategic Typology, in addition to the strategic integration between these approaches. This yet to develop a field research so that it could compare through factor analysis and cluster the results of that research with the theory. Examined the perceived strategies in each of the clusters identified. It concluded that the more strategic choices are aligned with the theoretical model, better the perception of the perfor
Keywords: análise de Cluster - desempenho percebido; integração estratégica; levantamento; estratégia percebida; analysis of Cluster - noticed performance; strategic integration; survey; noticed strategy; Ciências Sociais Aplicadas